2011
DOI: 10.1097/mlr.0b013e3182028954
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study Using a National Administrative Database to Determine the Impact of Hospital Volume on Compliance With Clinical Practice Guidelines

Abstract: This study demonstrated that hospital volume was significantly associated with compliance with CPGs and that the Japanese administrative database was a viable tool for the monitoring of compliance with CPGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 37 publications
0
54
0
Order By: Relevance
“…The literature review carried out by the IRDES shows that for certain procedures and interventions, particularly complex surgery, there is a real possibility of improving outcomes by increasing activity volumes 7) . Our previous literatures have showed the volume outcome relationship for various clinical interventions 6), 8) . All these results have suggested that it would be better to concentrate the surgical cases into selected facilities in order to ameliorate the efficiency of care in the case of relatively rare pathologies.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The literature review carried out by the IRDES shows that for certain procedures and interventions, particularly complex surgery, there is a real possibility of improving outcomes by increasing activity volumes 7) . Our previous literatures have showed the volume outcome relationship for various clinical interventions 6), 8) . All these results have suggested that it would be better to concentrate the surgical cases into selected facilities in order to ameliorate the efficiency of care in the case of relatively rare pathologies.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Higher hospital case volume, expressed as the number of cases during the study period, was associated with higher compliance with the clinical practice guideline for acute cholangitis. 6 Furthermore, in upper gastric cancer patients who underwent endoscopic submucosal dissection (ie, a technique that enables complete en bloc resection of cancer with endoscopy), there was an inverse relationship between hospital case volume and dissection-related complications. 7 However, the occurrence of related complications was similar across hospital case volumes for the dissection of middle-to-lower gastric cancer.…”
Section: Article P 2327mentioning
confidence: 99%
“…We selected CPGs for acute cholangitis 6) . These CPGs were posted in the Journal of Heapto-Biliary-Pancreatic Surgery in 2007 [7][8][9][10][11][12] .…”
Section: Database On Evaluation Of the Relationship Between Hospital mentioning
confidence: 99%
“…This dataset contains a detailed procedure information. Using this dataset we have evaluated the relationship between hospital volume and compliance with CPGs for acute cholangitis 6) . The results are very interesting in showing that hospital volume was significantly correlated with compliance with CPGs and that compliance level was significantly correlated with in-hospital mortality 6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation